PENYULUHAN MANFAAT BUMBU MASAK SEBAGAI SUMBER ANTIOKSIDAN ALAMI MENJAGA KESEHATAN DI MASA PANDEMI - Mauizatul Hasanah; Hilma Hilma; Ensiwi Munarsih; Romsiah Romsiah; Septiani Martha (JUARA: Jurnal Wahana Abdimas Sejahtera, 2022)
This community service activity for STIFI Bhakti Pertiwi lecturer was held by conducting outreach to the community, namely MTS Al-Hikmah teacher. Counseling about the benefits of cooking spices as a source of natural antioxidants is carried out to provide education to the public about the use of local fresh ingredients in maintaining a healthy body, especially during the pandemic. This activity is carried out online, with the delivery of material about the benefits of antioxidants for the body, sources of antioxidants, antioxidant cooking spices and thier benefits and chemical content. The result of this activity is that people gain knowledge about antioxidants and their sources in daily food ingredients. Implementing lecturers who also represent campuses have succeeded ini making counseling activities a campus communication medium in conveying knowledge to the public. This service activity is very beneficial for the community